Contemporary Problems of Nautical Tourism Development in Croatia - Favro, Srećko; Glamuzina, Nikola (Promet - Traffic&Transportation, 2005)
The paper deals with the problems that have arisen due tothe rapid development of nautical tourism on the Croatiancoast. The fact is that Croatia, unlike other Mediten·aneantourist countries still does not control nautical tourism developmentin the sense of spatial planning and implementation ofspecific laws. There are other problems that are generated bythe growing number of tourists in Croatian marinas and unevengeographic distribution of ports.